Usia Ibu Dengan Kecemasan Ibu Hamil Trimester III Dalam Menghadapi Persalinan Di Masa Pandemi Covid-19 Tahun 2022 - Sartika Dwi Yolanda Putri; Harlinda Widia Putri (Jurnal Anestesi, 2023)
Anxiety is felt most acutely in vulnerable and high-risk populations during the COVID-19 pandemic, namely pregnant women. Excessive anxiety causes levels of stress hormones in the body to increase and inhibits cervical dilation, resulting in prolonged labour. Long delivery is one of the causes of high maternal mortality rates in Indonesia. This study aims to determine the age and anxiety of third trimester pregnant women in facing childbirth during the COVID-19 pandemic in 2022. The research design used was Cross-Sectional with an analytical survey method. Sampling by purposive sampling technique, a sample of 74 respondents. Data were analyzed by univariate and bivariate. The results showed that there was a relationship between age and third-trimester pregnant women's anxiety in facing childbirth in 2022 with a contingency coefficient value of C = 0.315 which was low (0.20-0.399).